KONSEP AWAL WAKTU SALAT IMAM GHOZALI DARI PERSPEKTIF FIQH DAN ASTRONOMI - Muhammad Najib; M. Ihtirozun Ni'am; Dwi Oktarini (MIYAH : Jurnal Studi Islam, 2022)
Abstract: Prayer is the most important worship in Islam. Discussing prayer, it will not be separated from the conditions for the validity of prayer, namely the entry of prayer times. The beginning of the prayer time is determined based on the position of the sun concerning the earth, thus calculating the beginning of the prayer time is calculating when the sun occupies certain positions while circling the earth, namely when the dawn of Sadiq, the sun slips when the shadow of an object is the same as the shadow of the object itself, the sun sunset and the loss of the red twilight. In determining the beginning of this prayer time, there is a dichotomy/difference in interpretation. Among the different forms of interpretation when determining the start of the Zuhur prayer time, when the shadow of an object is as long as the object itself and the shadow of an object is twice the length of the object. Especially in the book Ihya Ulumuddin, Imam Al-Ghazali, has his own opinion about the beginning of prayer time, when in an area you cannot see the sun setting in the west because it is blocked by a mountain such as, then look towards the east, see black bursts in the sky, then it is the same as a sign of the entry of maghrib time, and the beginning of the time for the Isha prayer, marked by the loss of the red twilight, if in an area covered and blocked by mountains to see the disappearance of the red twilight in the west, then look at the small stars that appear in the east, then that is an early sign of entering the time for the Isha prayer. The method used is qualitative, referring to books, journals, and theses that are commensurate with the discussion to be raised. Keyword: Early prayer time, ihya Ulumuddin, fuqaha, Imam Al-Ghazali